MANAGEMENT STRATEGIES IN MANAGING LIVE STREAMING PLATFORM SHOPEE TO IMPROVE FOOTWEAR PRODUCTS AT CV. BD INDONESIA - Nadiya Kharisma Wulandari (Pedagogic Research-Applied Literacy Journal, 2026)
This study aims to identify and analyze the management strategies implemented at CV. BD Indonesia through the live streaming platform on Shopee in utilizing the live streaming feature as a marketing tool. Shopee, as a leading e-commerce platform, has developed live streaming as one of the channels to increase interaction with consumers and strengthen sales of footwear products at CV. BD Indonesia. This study uses a qualitative approach with a case study method to explore how Shopee designs and manages live streaming content and evaluates its impact on consumer experience and marketing effectiveness. The results of the study indicate that the live streaming management strategy at Shopee includes selecting influencers or presenters who have high appeal, optimizing broadcast time, and using interactive features.